The Influence of Accounting System and Fiscal Policy on Regional Development - Bogdan, Oana; Mateș, Dorel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Regional development is a concept that aims at stimulating and diversifying economic activities, stimulating private sector investment and it contributes to reducing unemployment and improving living standards. To achieve these goals accounting and tax policies are necessary to allow private operators to realize taxable income, to create jobs for people and to pay taxes and contributions due to the State budget. The State must reinvest a part of the resources collected to the community in order to improve infrastructure, education and health, thus contributing to regional development. Changes in tax law and accounting adopted in Romania during 2009-2014 are regarded as tax breaks for companies created to ensure economic growth, dynamic and sustainable through efficient use of regional and local potential. In this paper we analyze the influence of the accounting and fiscal system on the regional development given that these measures do not always achieve their objectives established companies having benefit from the application of various tax measures. The paper will present the main changes of the tax and accounting systems and their impact on the regional development in Romania and the consequences resulting in implementing these measures.